Storytelling as a Literacy Strategy to Improve Reading and Language Ability in Phase A: Mendongeng sebagai Strategi Literasi untuk Meningkatkan Kemampuan Membaca dan Berbahasa pada Fase A - Supriyadin, Supriyadin; Wiarsih, Asih; Supriatin, Asep; Afifah, Riska; Latifah, Ufi (CV. Media Publikasi Profesional, 2025)
Low reading interest among children has become a growing concern, considering that literacy skills serve as a foundational element in developing the quality of human resources. To address this issue, effective strategies are needed to increase children's engagement with reading. This study explored the use of storytelling as a literacy strategy to foster interest in reading and language development. A qualitative descriptive method was employed, using direct observation at the Pelita Community Reading Park (TMB) located in Cirebon Regency. The observations revealed that the storytelling method significantly improved children's reading interest, text comprehension, and verbal expression. Children became more engaged in listening, understanding, and applying new vocabulary in daily conversations. Furthermore, storytelling proved effective in creating a joyful learning environment and promoting early literacy development. Based on these findings, the study recommends integrating storytelling literacy into early-grade language instruction, particularly within elementary education, as a comprehensive strategy to enhance children's language ability.